A Very Short, Fairly Interesting and Reasonably Cheap Book About Studying Strategy - Carter, Chris (SAGE Publications, Ltd. (UK), 2008)
′If strategy is the queen of business, then this book offers us the perfect introduction to her court! It is accessible, lively, and informative. The book repays the reader with wonderful account of how strategy works. It also lets the reader in on some of the darker secrets of strategy′ -  André Spicer, Associate Professor of Organisation Studies, Warwick Business School Studying Strategy is a welcoming, lively and thought provoking account that helps students get to grips with strategy′s key issues and broad debates and introduce them to the latest ideas. Conceived by Chris Grey as an antidote to conventional textbooks, each book in the ‘Very Short, Fairly Interesting and Reasonably Cheap’ series takes a core area of the curriculum and turns it on its head by providing a critical and sophisticated overview of the key issues and debates in an informal, conversational and often humorous way. Suitable for students of strategy at Undergraduate, Masters and MBA level, professionals involved in strategic decision making and anyone interested in how strategy works.